Preparation and characterization of silver nanoparticles-reduced graphene oxide on ITO for immunosensing platform - Jamil, A.; Lim, Hong Ngee; Yusof, Nor Azah; Ahmad Tajudin, Asilah; Huang, N. M.; Pandikumar, A.; Golsheikh, A. Moradi; Lee, Y. H.; Andou, Y. (Elsevier, 2015)
We here report the in-situ electrochemical deposition of silver nanoparticles (AgNPs) and a reduced graphene oxide (rGO) nanocomposite on the surface of an indium tin oxide (ITO) electrode. The nanocomposite modified ITO was used as a basic platform for the construction of a novel electrochemical biosensor for the detection of hydrogen peroxide (H2O2); where horseradish peroxidase (HRP) tagged antibodies acted as recognition elements for carcinoembryonic antigen (CEA). The AgNPs-rGO/ITO modified electrode remarkably outperformed a bare electrode because of its enhanced surface area and electrocatalytic activity, resulting in a notably amplified electrical signal for the detection of H2O2. Through a cyclic voltammetric (CV) technique, the detection limit of the sandwich type immunoassay configuration was found to be 214 μM, with a linear range of 25–500 μM, as compared to the non-sandwich system, which was 120 μM with the same linear range. In contrast, the current–time response of the resulting sandwich-type immunoassay configuration showed a wider linear response to H2O2 in the range of 25–1450 μM, with a detection limit of 5.3 μM, while the non-sandwich system exhibited a linear range of 25–1355 μM (R2 = 0.9992), with a detection limit of 10 μM. Therefore, the current–time response provided a more sensitive means of detecting H2O2. The resulting immunosensor also exhibited outstanding stability and reproducibility, as well as selectivity toward H2O2 in the presence of several interferences.